Comparative study of constitutive modeling for Ti–6Al–4V alloy at low strain rates and elevated temperatures - Kotkunde, Nitin; Deole, Aditya D.; Gupta, Amit Kumar; Singh, Swadesh Kumar (Materials in engineering, 2014)
•Isothermal uniaxial tensile testing of Ti–6Al–4V alloy from 323K to 673K.•Constitutive modeling to predict the flow stress at elevated temperatures.•Comparison of constitutive models. An accurate prediction of flow behavior of metals considering the combined effects of strain, strain rate and temperature is essential for understanding flow response of metals. Isothermal uniaxial tensile tests have been performed from 323K to 673K at an interval of 50K and strain rates 10−5, 10−4, 10−3 and 10−2s−1. In this study prediction of flow behavior of Ti–6Al–4V alloy sheet is done using four constitutive models namely; Johnson–Cook (JC), Fields–Backofen (FB), Khan–Huang–Liang (KHL) and Mechanical Threshold Stress (MTS). The predictions of these constitutive models are compared using statistical measures like correlation coefficient (R), average absolute error (Δ) and its standard deviation (δ). Analysis of statistical measures revealed that FB model has more deviation from the experimental values. Whereas, the predictions of all other models (JC, KHL, and MTS) are very close to the experimental results. JC and KHL are better models for predicting the flow stress. However, considering the fact that MTS model is a physical based model, MTS model is preferred over other models.